PENGARUH MODEL PEMBELAJARAN INDEX CARD MATCH TERHADAP OPTIMALISASI HASIL BELAJAR MATEMATIKA PADA SISWA KELAS II SD - Nabila Yulia Adinda; Jayanti; David Budi Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Index Card Match learning model onoptimizing mathematics learning outcomes in the material of whole numbers ofgrade II students of SD Negeri 077 Palembang. The study used a quasi-experimental method with a Non-Equivalent Control Group Design. The researchsample consisted of two classes, namely the experimental class using the IndexCard Match model and the control class using the conventional method. The datacollection instrument was in the form of 10 multiple-choice questions given duringthe pretest and posttest. The results of the analysis showed a significant increasein learning outcomes in the experimental class compared to the control class. Thisis evidenced by the results of the t-test which obtained a significance value (Sig. 2-tailed) < 0.05, which indicates a significant effect of the use of the Index CardMatch model on students' mathematics learning outcomes. This model has beenproven to be able to increase students activeness, motivation, and understandingof the material of whole numbers through interactive matching of question andanswer cards. Thus, the use of the Index Card Match learning model can be analternative effective learning strategy in improving mathematics learning outcomesin elementary schools.